High-resolution palaeomagnetic record from Sea of Marmara sediments for the last 70 ka - Makaroğlu, Özlem; Nowaczyk, Norbert R; Eriş, Kadir K; Çağatay, M Namık (Geophysical Journal International, 2020)
Magnetostratigraphic and geochemical analyses were performed on two sediment cores recovered from the Sea of Marmara to investigate geomagnetic field variations over the last 70 ka. A chronology for each of the two cores was developed from eight AMS 14C datings, tephrochronology, and tuning of Ca concentrations with stadials and interstadials observed in Greenland ice core oxygen isotope data. Based on the age models, cores MD01–2430 and MRS-CS19 reach back to 70 ka and 32 ka, respectively. High average sedimentation rates of 43 cm/kyr for core MD01–2430 and 68 cm/kyr for core MRS-CS19 allow high-resolution reconstruction of geomagnetic field variations for the Sea of Marmara. Mineral magnetic properties are sensitive to glacioeustatic sea-level changes and palaeoclimate variations in this region, reflecting the variable palaeoenvironmental conditions of the Sea of Marmara during last 70 ka. Despite the impairment of the palaeomagnetic record in some stratigraphic intervals due to early diagenesis, relative palaeointensity variations in the Sea of Marmara sediments correlate well with similar records derived from other regions, such as the nearby Black Sea and the GLOPIS-75 stack. The directional record derived from the Sea of Marmara cores exhibits typical palaeosecular variation patterns, with directional anomalies at 41 ka and 18 ka, representing the Laschamps and postulated Hilina Pali excursions, respectively. Both directional anomalies are also associated with palaeointensity minima. A further palaeointensity minimum at 34.5 ka is likely related to the Mono Lake excursion, with no directional deviation documented in the Sea of Marmara palaeomagnetic record so far.